2019
DOI: 10.1242/dev.175729
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-19b restricts Wnt7b to the hem, which induces aspects of hippocampus development in the avian forebrain

Abstract: In the Materials and Methods section, the service providers for in vitro Cas9 assay and Illumina Sequencing systems were not mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…E2f8 and Neurod1 (7,17). Now, to test the effect of miR-19b on E2f8 and Neurod1 mRNAs, we performed gain-offunction (GoF) and loss-of-function (LoF) experiments with miR-19b using expression construct for miR-19b and Sponge-19b, respectively (See materials and methods) (14), and found out that miR-19b is indeed sufficient to regulate the expression of E2f8 as well as Neurod1, whereas necessary for E2f8 expression but Neurod1 (Fig. 1H-K).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…E2f8 and Neurod1 (7,17). Now, to test the effect of miR-19b on E2f8 and Neurod1 mRNAs, we performed gain-offunction (GoF) and loss-of-function (LoF) experiments with miR-19b using expression construct for miR-19b and Sponge-19b, respectively (See materials and methods) (14), and found out that miR-19b is indeed sufficient to regulate the expression of E2f8 as well as Neurod1, whereas necessary for E2f8 expression but Neurod1 (Fig. 1H-K).…”
Section: Resultsmentioning
confidence: 99%
“…Further, to find out a cell-cycle regulator for this context, we used literature search and selected a microRNA, miR-19b that regulates proliferation in the mouse forebrain (13) and express in the chick pallial VZ at E4.5 (14). Our analysis showed miR-19b expression in the proliferating NPCs at VZ at E6.5 as well, as opposed to the Neurod1 in the SVZ (Fig.1E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant expression of miR-19 in the hippocampus causes dysregulated migration of developing neurons ( Han et al, 2016 ). In addition, miR-19 plays a key role in the positioning of the hippocampal tissue via Wnt-mediated signaling pathway ( Sindhu et al, 2019 ). It has been demonstrated that miR-29a, in addition to regulate neural morphology and soma size, targets mRNAs related to extracellular matrix proteins including Fibrillin1, Follistatin-like1(FSTL1) and Laminin subunit gamma-2 to control neuronal migration ( Ma et al, 2020 ).…”
Section: Micrornas Are Important Regulators Of Neural Development In ...mentioning
confidence: 99%
“…One of the key signaling centers in the mammalian CNS is the cortical hem (CH), which develops at the telencephalic dorsal midline, between the choroid plexus and cortical neuroepithelium ( Grove et al, 1998 ; Jones et al, 2019 ; Moore and Iulianella, 2021 ; Sindhu et al, 2019 ). The CH is necessary and sufficient for the development of the hippocampus in adjacent neuroepithelium ( Mangale et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%